The Expression of Concern “Evaluation of the antimicrobial potential of partially purified proteins/peptides of Yellow Scorpion Buthus sindicus against Carbapenem-Resistant Acinetobactor baumannii & Pseudomonas aeruginosa” [IJEHSR 9(2) (2021) 238-247] - Sehrish Urooj; Rafat Amin; Zeba Haque (International Journal of Endorsing Health Science Research, 2022)
This expression of concern related to the above-mentioned publication highlights the authorship dispute brought to our attention by third parties, which they further transformed into a data authorization claim against the first author (Corresponding Author). It was informed that third parties (Author’s Institution) formed a committee for evaluation, as per their inquiry the manuscript was submitted by the corresponding author without information to the other co-authors. Moreover, the committee has recommended the official retraction of the article due to an authorship claim by a co-supervisor who was not given due credit for his contribution to the work published. The authorship and data authorization issues were raised to the corresponding author and the institution involved for clarifications and investigations. The concern and this note will remain appended to the above-mentioned article, unless the Journal Ethical Committee, Author(s), and Third Party reach a suitable solution to the dispute and proof of misconduct.